(untitled) (Modern Problems of Metallurgy, 2025)
The aim of the study is to explore the theoretical foundations for improving energy consumption efficiency in the metallurgical industry under the conditions of global climate policy challenges, production transformation, and the need to reduce energy costs. The paper analyzes the main technological processes, the level of energy intensity in the industry, as well as international experience in implementing energy-efficient solutions. The methods. The research is based on an interdisciplinary analysis of scientific sources, industry reports, statistical data, and the techno-economic characteristics of steel production. Methods of comparative analysis of energy consumption for various technological routes and a systematic approach to assessing innovation potential are applied. Findings. It has been established that a significant portion of energy consumption is concentrated in blast furnace–converter processes. The transition to electric arc furnace (EAF) production, the implementation of hydrogen metallurgy, the use of secondary raw materials, and digital technologies (Industry 4.0) open up opportunities for a substantial increase in energy efficiency. Examples of successful modernization at enterprises in various countries are provided The originality. The study systematizes the factors that determine the energy intensity of production processes, reveals the relationship between technological changes and energy consumption structure, and substantiates the need for a comprehensive approach to the transformation of the industry Practical implementation. The results can be used for strategic planning of enterprise modernization, development of energy-saving investment projects, and the formation of national industrial decarbonization policies.